Ethnic tourism in El Salvador - Contreras granadero, Jessica Xiomara; Hernández Aldana, Catalina Concepción; Pleitez del Cid, EmelEn Abisag (2024)
Tourism in El Salvador has been leveled in recent years as an industry that can contribute to economic development. This paper tries to give an overview of tourism development from the perspective of Ethnic Tourism, considered as a valuable resource to be incorporated in the tourism field, to search for innovative strategies for promotion and maintenance, whereas sustainable development models provide alternatives to schedule conservation with economic and social aspects that opens tourism. In this paperwork is about the tourism and the importance that this has for the economical situation in El Salvador. Also, Ethnic Tourism is presented as a strategically way for the indigenous groups in the country. All this with the purpose of maintaining the culture and revive the identity of the Salvadoran people. In here, there are different segments like history of tourism in El Salvador, indigenous groups, the role of the society and the government with these peoples and the need to bring to development for these communities. Under this perspective there is the idea that Salvadoran government should give more support to the local indigenous people in order to develop the ethnic tourism in the country.